Arabic Translation Of English News: A Comparative Study Of Style And Message - Kadhim, Kais Amir (2008)
This study examines the Arabic translation of English BBC News. It compares the English ST and the TI from~ two angles: the style and the message. The objectives are to find out the nature of the stylistic changes that occur in the Arabic translation, to evaluate if the stylistic changes have affected the quality of the messages, to find out the extent to which the message is preserved in terms of field, tenor and mode, to find out the translating and the stylistic strategies that are likely to have been used by the translators. The study uses a comparative method and employs eclectically some ideas from the translation theory, structural (syntactic) theory, semantic theory, stylistics, pragmatics, cultural theory and sociolinguistic theory. The study shows that the changes in style are within the realm of syntax (sentences, clauses and phrases).